Neuregulin 1: a prime candidate for research into gene-environment interactions in schizophrenia? Insights from genetic rodent models - Karl, Tim (Frontiers in Behavioral Neuroscience, 2013)
Schizophrenia is a multi-factorial disease characterized by a high heritability and environmental risk factors. In recent years, an increasing number of researchers worldwide have started investigating the ‘two-hit hypothesis’ of schizophrenia predicting that genetic and environmental risk factors (GxE) interactively cause the development of the disorder. This work is starting to produce valuable new animal models and reveal novel insights into the pathophysiology of schizophrenia. This mini review will focus on recent advancements in the field made by challenging mutant and transgenic rodent models for the schizophrenia candidate gene neuregulin 1 (NRG1) with particular environmental factors. It will outline results obtained from mouse and rat models for various Nrg1 isoforms/isoform types (e.g. transmembrane domain Nrg1, Type II Nrg1), which have been exposed to different forms of stress (acute versus chronic, restraint versus social) and housing conditions (standard laboratory versus minimally enriched housing). These studies suggest Nrg1 as a prime candidate for GxE interactions in schizophrenia rodent models and that the use of rodent models will enable a better understanding of GxE interactions and the underlying mechanisms.